Policy maker and health care provider perspectives on reproductive decision-making amongst HIV-infected individuals in South Africa - Zweigenthal Virginia; Bracken Hillary; Myer Landon; Cooper Diane; Harries Jane; Orner Phyllis (BMC, 2007)
Abstract Background Worldwide there is growing attention paid to the reproductive decisions faced by HIV-infected individuals. Studies in both developed and developing countries have suggested that many HIV-infected women continue to desire children despite knowledge of their HIV status. Despite the increasing attention to the health care needs of HIV-infected individuals in low resource settings, little attention has been given to reproductive choice and intentions. Health care providers play a crucial role in determining access to reproductive health services and their influence is likely to be heightened in delivering services to HIV-infected women. We examined the attitudes of health care policy makers and providers towards reproductive decision-making among HIV-infected individuals. Methods In-depth interviews were conducted with 14 health care providers at two public sector health care facilities located in Cape Town, South Africa. In addition, 12 in-depth interviews with public sector policy makers and managers, and managers within HIV/AIDS and reproductive health NGOs were conducted. Data were analyzed using a grounded theory approach. Results Providers and policy makers approached the issues related to being HIV-infected and child bearing differently. Biomedical considerations were paramount in providers' approaches to HIV infection and reproductive decision-making, whereas, policy makers approached the issues more broadly recognizing the structural constraints that inform the provision of reproductive health care services and the possibility of "choice" for HIV-infected individuals. Conclusion The findings highlight the diversity of perspectives among policy makers and providers regarding the reproductive decisions taken by HIV-infected people. There is a clear need for more explicit policies recognizing the reproductive rights and choices of HIV-infected individuals.